Development of Boccia Throw Test Instrument for Athletes with Cerebral Palsy - Doewes, Rumi Iqbal; Nuryadin, Islahuzzaman; Hendarto, Singgih; Purnama, Sapta Kunta (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Boccia is an accuracy game for athletes with cerebral palsy. In a Boccia game, the players throw a red- or blue-colored leather ball towards a white-colored target ball called the jack. Points are awarded to the colored balls with the closest distance to the jack. Aims: This development research aims to design a Boccia throw test instrument for novice athletes with cerebral palsy and test the instrument's validity and reliability. Methods: We use research and development with a 6-step instrument development method by Gall, Gall, and Borg. The subject of this research was 20 novice Boccia athletes who completed six trials to test the validity and reliability of the test instrument. Analysis was conducted through corrected item-total correlation and Cronbach’s Alpha using SPSS. Results: This research has produced a boccia throwing test instrument for cerebral palsy athletes with a throwing target in the form of a circle diameter of 25 cm, which is placed 5 meters from the ball throwing area. This instrument has proven its validity and reliability based on the validity value on the corrected item-total correlation > 0.05 and the reliability value on Cronbach's alpha > 0.80. Conclusion: The resulting test instrument is valid and reliable to assess the Boccia throwing accuracy skill in novice players.